2013
DOI: 10.3892/or.2013.2288
|View full text |Cite
|
Sign up to set email alerts
|

Terrein induces apoptosis in HeLa human cervical carcinoma cells through p53 and ERK regulation

Abstract: Terrein, a fungal metabolite derived from Aspergillus terreus, has been shown to have a variety of biological activities in human cells including inhibition of melanogenesis, as well as anti-inflammatory, antioxidant and anticancer properties. In the present study, terrein was shown to have marked anticancer activity on HeLa human cervical carcinoma cells. Terrein exhibited inhibition of proliferation within the same ranges for other cancer cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
(47 reference statements)
2
31
0
Order By: Relevance
“…The compound has been tested against different types of cancer cell lines such as pancreatic cancer, breast cancer (Liao et al, 2012), human cervical cancer (Porameesanaporn et al, 2013) skin cancer, and prostate cancer (Arakawa et al, 2008). Among the different types of cancer identified globally, lung cancer is found to be the most prevalent type (12.7% of 1.61 million) (Ferlay et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The compound has been tested against different types of cancer cell lines such as pancreatic cancer, breast cancer (Liao et al, 2012), human cervical cancer (Porameesanaporn et al, 2013) skin cancer, and prostate cancer (Arakawa et al, 2008). Among the different types of cancer identified globally, lung cancer is found to be the most prevalent type (12.7% of 1.61 million) (Ferlay et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Specific biomarkers are required for the early diagnosis and prediction of metastatic progression and effective therapy. However, there is currently no efficient therapy against cervical cancer and the available treatments have various disadvantages (1,1621). It has been shown that inactivation of tumor suppressor genes and activation of oncogenes is significant in carcinogenesis, and results from genetic and epigenetic alterations (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of terrein ( Fig. 1) was performed as previously described (11). Briefly, an ethyl acetate (EtOAc) extract from the culture broth of Aspergillus terreus CRI301 was concentrated in vacuo, fractioned and purified by Sephadex™ LH-20 using MeOH as an eluent.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the caspase-7 pathway and suppression of Akt signaling was observed following exposure of ABCG-2-expressing MCF-7 breast cancer cells to terrein (10). HeLa cervical cancer cells were also sensitive to the anti-proliferation activity of terrein which was mediated through induction of apoptosis (11). In addition, terrein attenuated angiogenin production in head and neck cancer cells (12), which may be another underlying mechanism in its anticancer effects.…”
Section: Introductionmentioning
confidence: 99%